The interplay of gender, social context, and long-term unemployment effects on subjective health trajectories - Laura Altweck; Stefanie Hahm; Holger Muehlan; Tobias Gfesser; Christine Ulke; Sven Speerforck; Georg Schomerus; Manfred E. Beutel; Elmar Brähler; Silke Schmidt (BMC, 2021)
Abstract Background While a strong negative impact of unemployment on health has been established, the present research examined the lesser studied interplay of gender, social context and job loss on health trajectories. Methods Data from the German Socio-Economic Panel was used, which provided a representative sample of 6838 participants. Using latent growth modelling the effects of gender, social context (East vs. West Germans), unemployment (none, short-term or long-term), and their interactions were examined on health (single item measures of self-rated health and life satisfaction respectively). Results Social context in general significantly predicted the trajectories of self-rated health and life satisfaction. Most notably, data analysis revealed that West German women reported significantly lower baseline values of self-rated health following unemployment and did not recover to the levels of their East German counterparts. Only long-term, not short-term unemployment was related to lower baseline values of self-rated health, whereas, in relation to baseline values of life satisfaction, both types of unemployment had a similar negative effect. Conclusions In an economic crisis, individuals who already carry a higher burden, and not only those most directly affected economically, may show the greatest health effects.